PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENURUNAN PENYALAHGUNAAN SMARTPHONE DI KELAS XI ADP SMK MUHAMMADIYAH 2 PEKANBARU TAHUN AJARAN 2014/2015 - Dedi Setiadi Setiadi; Zulfan Saam Saam; Tri Umari Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The title of this research is the effect of guidance services group to the decline in smartphone abuse. This research aims to: 1)To know the smartphone abuse before this service do. 2)To know the process of guidance services group to the decline in smartphone abuse. 3)To know the smartphone abuse after this service did. 4)To know the decline of smartphone after and before this service do. 5)To know the effect of guidance services group to the decline in smartphone abuse. The method of this research is quasi experiment with one-group pretest–posttest designe.The subjects of this research are the students who use smartphone abuse in class XI ADP. Based on the research result obtained conclusion with regard to the effect of group guidance to do decline in smartphoneabuse, like, a)Before being given the guidance of the group is in the category of high 16,67%, medium 66,66%, low 16,67%. b)From the process that have been implementing the writer found that the smartphone abuse is inclined to quiet students. c)After the group counseling gave the high category is 6,66%, medium 46,67, low 46,67. d)There is a significant effect between before and after giving guidance group to decline smartphone abuse based on test “t”. Where there is thitungbigger than ttablein 5%level. e)Based on the determine coefficient calculation got r20,26 which mean get 26% guidance services group contribution to smartphone abuse decrease from students class XI ADP SMK Muhammadiyah 2 Pekanbaru. Keyword : Group Guidance,Smartphone misappropriation